The Implementation of Classical Guidance Services with Mystery Paper Games to Improve Elementary School Students' Learning Concentration - Najikhatunnisa' Najikhatunnisa'; Nabila Rizqi; Lailin Ni’mah; Evilia Kusuma; Ade Sucipto (Jurnal Prasasti Ilmu, 2026)
This study was conducted to identify the implementation of classical guidance services using paper mystery games in improving the learning concentration of elementary school students. This study used a qualitative method with a descriptive approach, with the research subjects being 31 fifth-grade students at SD N 6 Cendono. This was done through interviews, questionnaires, observations of the implementation of classical guidance services, and documentation collection. Data analysis was carried out through data reduction stages, descriptive data presentation, and drawing conclusions based on findings obtained in the field. The results of the study showed that the level of student learning concentration was still relatively low, which was characterized by students being easily distracted, paying less attention to learning, and having difficulty concentrating during the learning process. and often talking during learning. Several contributing factors included the classroom environment, interactions with peers, and the varying individual conditions of students. The implementation of classical guidance services with paper mystery games provided positive results, where students became more active, enthusiastic, brave in expressing opinions, and more concentrated during the learning process. Classical guidance services with the mystery game method can be used as an effective effort to improve the learning focus of elementary school students.